2021
DOI: 10.1097/gox.0000000000003420
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inflammatory and Fibrotic Aspects of Tissue Remodeling of Acellular Dermal Matrix in a Nonhuman Primate Model

Abstract: Background: Human acellular dermal matrices (hADMs) are applied in various soft tissue reconstructive surgeries as scaffolds to support tissue remodeling and regeneration. To evaluate the clinical efficacy of hADM implants, it is integral that the hADM does not induce a host chronic inflammatory response leading to fibrotic encapsulation of the implant. In this study, we characterized the inflammatory and fibrosis-related tissue remodeling response of 2 commercial hADM products (SimpliDerm and AlloD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Per AlloDerm’s Instructions For Use (IFU), electron beam irradiation is used to sterilize AlloDerm RTU to a Sterility Assurance Level (SAL) of 10 -3 whereas SimpliDerm’s IFU states that it is terminally sterilized to a SAL of 10 -6 using a proprietary ionizing radiation system. While these processing methods may not affect extracellular matrix stability, the divergent sterility levels could affect microbial colonization vulnerability [ 15 ]. Other potential benefits of the proprietary processing methods of SimpliDerm have been elucidated in rigorous preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Per AlloDerm’s Instructions For Use (IFU), electron beam irradiation is used to sterilize AlloDerm RTU to a Sterility Assurance Level (SAL) of 10 -3 whereas SimpliDerm’s IFU states that it is terminally sterilized to a SAL of 10 -6 using a proprietary ionizing radiation system. While these processing methods may not affect extracellular matrix stability, the divergent sterility levels could affect microbial colonization vulnerability [ 15 ]. Other potential benefits of the proprietary processing methods of SimpliDerm have been elucidated in rigorous preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential benefits of the proprietary processing methods of SimpliDerm have been elucidated in rigorous preclinical studies. For example, a non-human primate model demonstrated that SimpliDerm facilitates host responses that foster remodeling of the hADM into native tissue [ 15 ]. In that study, SimpliDerm demonstrated a milder initial inflammation, more gradual implant degradation, reduced expression of profibrotic genes, and reduced long-term inflammatory markers compared to the host response to AlloDerm RTU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in a recent preclinical study, the intact ECM of SimpliDerm enhances and supports neovascularization, cell migration, tissue incorporation, and a modulated immune response that fosters remodeling of the hADM into native tissue. 15 …”
Section: Discussionmentioning
confidence: 99%
“…HADM is both cell-free and major histocompatibility complex (MHC) -free; it does not trigger immune rejection, and it has good histocompatibility. To ensure the safety and efficacy of HADM in clinical applications, investigators have evaluated its possible host-graft rejection and fibrotic reactions in animal experiments ( 5 , 6 ). To date, HADM has been successfully used in the repair of urethral stricture, with positive clinical effects ( 7 ).…”
Section: Introductionmentioning
confidence: 99%